2008
DOI: 10.1524/ncrs.2008.0171
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 5-benzoyl-2-(2-chlorophenyl)-4-phenyl-2-oxazoline, C22H16ClNO2

Abstract: C 22 H 16 ClNO 2 ,monoclinic, P12 1 /n1(no. 14), a =10.6113(7) Å, b =9.6680(6) Å, c =17.176(1) Å, b =92.910(1)°, V =1759.8 Å 3 , Z =4,Rgt(F) =0.045, wRref(F 2 ) =0.111, T =100 K. Source of materialAs olution of trans-2-bezoyl-N-(2-chlorobenzoyl)-3-phenylaziridine (0.361 g, 1.0 mmol) in CH 3CN (15 ml) and NaI (0.2 mmol) was stirred at 50°C for 6h ours. Then the mixture was rinsed twice with water, the organic layer was separated and dried with anhydrous Na 2 SO 4 .E vaporation of the solvent under reduced press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Most of them suffer at least from one of the following disadvantages: (1) high costs of preparations, (2) long reaction times, (3) hygroscopicity, (4) no selectivity, (5) photosensitivity, (6) dangerous procedures for their preparation, and (7) tedious work-up procedures. [21][22][23][24][25][26][27][28][29][30][31][32] In continuation of our previous works, on oxidation and synthesis of heterocyclic compounds, [33][34][35][36][37][38][39] we now introduce an efficient, mild and rapid method for the oxidation of urazoles to their corresponding 4-substituted-1,2,4-triazole-3,5-diones (TADs), by using benzyltriphenylphosphonium nitrate (I, BTPPN) as a mild and novel oxidising reagent which is readily prepared by reaction of an aqueous solution of benzyltriphenylphosphonium chloride with NaNO 3 solution at room temperature (Scheme 1).…”
mentioning
confidence: 99%
“…Most of them suffer at least from one of the following disadvantages: (1) high costs of preparations, (2) long reaction times, (3) hygroscopicity, (4) no selectivity, (5) photosensitivity, (6) dangerous procedures for their preparation, and (7) tedious work-up procedures. [21][22][23][24][25][26][27][28][29][30][31][32] In continuation of our previous works, on oxidation and synthesis of heterocyclic compounds, [33][34][35][36][37][38][39] we now introduce an efficient, mild and rapid method for the oxidation of urazoles to their corresponding 4-substituted-1,2,4-triazole-3,5-diones (TADs), by using benzyltriphenylphosphonium nitrate (I, BTPPN) as a mild and novel oxidising reagent which is readily prepared by reaction of an aqueous solution of benzyltriphenylphosphonium chloride with NaNO 3 solution at room temperature (Scheme 1).…”
mentioning
confidence: 99%
“…Here we report synthesis of N-acyl ketoaziridines from the corresponding ketoaziridines with acyl chlorides. Then N-acyl ketoaziridines in the presence of a nucleophilic and Lewis acids afforded oxazolines [40][41][42].Although a few methods have been described for the preparation of N-acyl aziridines none of them described direct synthesis of oxazolines from N-H aziridines with carboxylic acid .In continuation of our recent interest in the reaction of ketoaziridines [48] and success for using Polyoxometalates [49], herein, we report a one-pot regio-and stereo-selective synthesis of trans-4-benzoyloxazolines, catalyzed by the K 5 [PW 11 ZnO 39 ].23H 2 O catalytic system with moderate to good yields under mild conditions. Abstract A new and one-pot synthesis of oxazolines has been accomplished by K 5 [PW 11 ZnO 39 ].23H 2 O-catalyst acylation followed by C-N ring opening/C-O bond formation in NH ketoaziridines.…”
mentioning
confidence: 99%
“…Here we report synthesis of N-acyl ketoaziridines from the corresponding ketoaziridines with acyl chlorides. Then N-acyl ketoaziridines in the presence of a nucleophilic and Lewis acids afforded oxazolines [40][41][42].…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Previous reports have shown that replacement of the hydrogen of the N-H moiety with an electron-withdrawing substituent increases the susceptibility of N-H aziridines to ring-opening or ring-enlargement reactions. [28][29][30] So, our first aim was to synthesize N-Boc-substituted ketoaziridines as a precursor for preparation of the corresponding nitrogen-containing compounds via ring opening or ring enlargement.…”
mentioning
confidence: 99%
“…Based on the well-documented transformation of Nacyl-or N-Boc-substituted aziridines into oxazolines in the literature [31][32][33][34] and our success 20,21 with the ring-expansion reaction of N-acyl-substituted aziridines with sodium iodide, we envisioned that ring expansion of 1a with (Boc) 2 O in the presence of sodium iodide might be similarly achieved to give oxazolidin-2-one 6a in a one-pot reaction. Thus, we examined the reaction of aziridine 1a with (Boc) 2 O in the presence of sodium iodide in acetone for achieving this aim; however, no reaction occurred, even under refluxing conditions (Table 1, entry 5).…”
mentioning
confidence: 99%